Editorial Note on Delayed Publication - Chief, Editor in (Journal of Environmental Science and Natural Resources, 2025)
We would like to extend our sincerest apologies for the delay in the publication of this issue. The postponement was due to a combination of unavoidable circumstances that impacted the editorial workflow and review process. Key contributing factors included unavailability of quality manuscripts, unforeseen administrative challenges, country’s political turmoil, delays in the peerreview cycle, and scheduling conflicts among contributors and reviewers. Additionally, technical difficulties in finalizing the formatting and layout further extended the timeline. We recognize the importance of timely communication in academic publishing and deeply regret any inconvenience this delay may have caused to our readers, authors, and contributors. Please be assured that we are taking necessary steps to streamline our processes and prevent similar occurrences in the future. We appreciate your understanding and continued support.